2023
DOI: 10.1007/s11696-023-02856-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impacts of simple electrolytes and hydrotrope on the interaction of ceftriaxone sodium with cetylpyridinium chloride at numerous study temperatures

Abstract: Herein, interactions between cetylpyridinium chloride (CPC) and ceftriaxone sodium (CTS) were investigated applying conductivity technique. Impacts of the nature of additives (e.g. electrolytes or hydrotrope (HDT)), change of temperatures (from 298.15 to 323.15 K ), and concentration variation of CTS/additives were assessed on the micellization of CPC + CTS mixture. The conductometric analysis of critical micelle concentration (CMC) with respect to the concentration reveals that the CMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 81 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Although many works have been reported on the cloudy generation and micellization of surfactants in the manifestation of drugs, 38–45 the behavior of the respective processes in the presence of ammonium-based salts is still unknown. Rub et al 42 reported the phase partition and assembly of TX-100/TTAB + metformin hydrochloride drug solutions in different hydrotropic media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many works have been reported on the cloudy generation and micellization of surfactants in the manifestation of drugs, 38–45 the behavior of the respective processes in the presence of ammonium-based salts is still unknown. Rub et al 42 reported the phase partition and assembly of TX-100/TTAB + metformin hydrochloride drug solutions in different hydrotropic media.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we studied the interaction of TTAB/TX-100 with PMH in potassium salts/alcoholic additives. 44,45 Herein, we explore the impacts of (i) concentrations of ammonium-based electrolytes on CMC and CP of a working system, (ii) temperature on TTAB + PMH micellization in ammonium salt system; (iii) thermodynamic variables (free energy (Δ G 0 m /Δ G 0 c ), enthalpy (Δ H 0 m /Δ H 0 c ) and entropy (Δ S 0 m /Δ S 0 c )), and (iv) enthalpy–entropy compensation variables of micellization/clouding processes in the attendance of employed salts.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, researchers have tirelessly engaged in investigating how medicines do interaction with surfactants, as surfactants are most frequently employed in the pharmaceutical industries and other applications. [1][2][3][4][5][6][7] These species have long been utilized in making drugs soluble in body uids and pharmaceutical production. It is essential to study the drug-surfactant interactions in order to create novel therapeutic formulations and pharmaceutical delivery methods.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation structures generated by surfactants have gained remarkable attention owing to their unique phenomenon. Due to their extraordinary behavior, surfactants are engaged in diverge functions for several research purposes including industrial studies. They are employed in many sectors of fundamental as well as advanced applications. The binding interaction of some active organic molecules with surfactants has been reported and displayed great importance in the arenas of surface chemistry. Surfactants also work as a simple pseudophase model in several studies conducted by many potential investigators through micelle-involved reactions. …”
Section: Introductionmentioning
confidence: 99%